Piezo-energy Harvesting and Application Prospects - Tiwari S.; Maiti P. (My University, 2025)
Energy is a fundamental need for all actions and activity. The continual exhaustion of traditional energy sources and their adverse effects on the environment have brought the globe to the point where alternative energy is the only viable solution. Energy harvesting using piezoelectric technology has drawn more attention as a different type of energy. A number of materials have been created that have demonstrated notable effectiveness in the field of piezoelectric energy harvesting. Electroactive materials have generated a lot of interest since they can be added to the matrix as a reinforcer to improve the electromechanical response and its application. Electroactive materials produce a superior polar phase, which makes them a good choice for piezoelectric energy harvesting due to their capacity to provide a better piezo-property. Piezoelectric materials are employed in a variety of applications, including wearable technology, actuators, biomedicine, and healthcare, because of their superior efficacy and endurance. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.